A relação juventude-trabalho no projovem integrado do município de Natal/RN - Santos, Luana Isabelle Cabral dos (2013)
The National Program for Youth Inclusion (ProJovem) has been created in 2005 in order to break the reproductive cycle of social inequality, through the improvement of the basic education and the professional qualification. Therefore, our objective is to discuss how the categories youth-work are inserted and implemented on ProJovem Integrado , which could be translated as Integrated , in Natal/RN. In 2008, ProJovem is has started to be executed based in four modalities: (1) Teenagers Socio-Educational Service, (2) Urban, (3) Worker and (4) Countryside Land Knowledge, aiming to serve a population from 15 to 29 years old who were seldom helped by specifics policies so far. In order to implement this research, three semi-structured interviews have been made, as well as observations at the program units and analysis of the official documents. In Natal, the operating modalities are: ProJovem Urban, which three units, divided in two districts of the city; the ProJovem Teenagers , which has ten units on Natal s four administrative regions; and ProJovem Worker , which were still structuring its courses until the beginning of the data collection. The data has been qualitatively analyzed through the Marxian Theory, tied to the Constant Comparative Method. The referred approach, based on the Grounded Theory, enables the understanding of the phenomenon s meanings through the perspective of the participants. The neighborhoods in which ProJovem s units are inserted has been characterized as well the Program s target. The results have been presented in three blocks: a) the modality s structure, which includes the implementation, functioning and operationalization of the activities; b) management of the modality s management, concerned to the main difficulties, expectations and functions; and c) the relation youth-work at the modalities. About the objectives and qualification and insertion goals, there is incongruence at the offer of occupational arches. We have observed that offered occupations are historically subservient and precarious. Hence they do not promote significant changes on the students career paths by usually inserting them into informal jobs or underemployments. Besides that, the professional qualification is very incipient. For that reason, it does not go with the necessary requirements to enable the youngster to enter the work world. It is considered that other researches are necessary to for better understanding of the remaining aspects of the relation youth-work